Approach to Sustainability-Based Assessment of Solution Alternatives in Early Stages of Product Engineering - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Sustainable product engineering is becoming increasingly important. This includes the development of environmentally friendly products and the design for recycling. In this paper a holistic method for the assessment of solution alternatives is presented, in which the stakeholder perspectives along the generic product lifecycle are taken into account. Finally, a new visualization is presented. By visualizing the results in the integrated sustainability triangle, decision-makers in product development can holistically assess the sustainability of the solution alternatives.
Keywords: sustainability; decision making; generic product lifecycle; design analysis; ecodesign